Frequencies of region of difference 1 antigen-specific but not purified protein derivative-specific gamma interferon-secreting T cells correlate with the presence of tuberculosis disease but do not distinguish recent from remote latent infections - Hinks, Timothy S C; Dosanjh, Davinder P S; Innes, John A; Pasvol, Geoffrey; Hackforth, Sarah; Varia, Hansa; Millington, Kerry A; Liu, Xiao-Qing; Bakir, Mustafa; Soysal, Ahmet; Davidson, Robert N; Gunatheesan, Rubamalar; et al. (Infection and immunity, 2009)
The majority of individuals infected with Mycobacterium tuberculosis achieve lifelong immune containment of the bacillus. What constitutes this effective host immune response is poorly understood. We compared the frequencies of gamma interferon (IFN-gamma)-secreting T cells specific for five region of difference 1 (RD1)-encoded antigens and one DosR-encoded antigen in 205 individuals either with active disease (n = 167), whose immune responses had failed to contain the bacillus, or with remotely acquired latent infection (n = 38), who had successfully achieved immune control, and a further 149 individuals with recently acquired asymptomatic infection. When subjects with an IFN-gamma enzyme-linked immunospot (ELISpot) assay response to one or more RD1-encoded antigens were analyzed, T cells from subjects with active disease recognized more pools of peptides from these antigens than T cells from subjects with nonrecent latent infection (P = 0.002). The T-cell frequencies for peptide pools were greater for subjects with active infection than for subjects with nonrecent latent infection for summed RD1 peptide pools (P <or= 0.006) and culture filtrate protein 10 (CFP-10) antigen (P = 0.029). Individuals with recently acquired (<6 months) versus remotely acquired (>6 months) latent infection did not differ in numbers of peptide pools recognized, proportions recognizing any individual antigen or peptide pool, or antigen-specific T-cell frequencies (P >or= 0.11). The hierarchy of immunodominance for different antigens was purified protein derivative (PPD) > CFP-10 > early secretory antigenic target 6 > Rv3879c > Rv3878 > Rv3873 > Acr1, and the hierarchies were very similar for active and remotely acquired latent infections. Responses to the DosR antigen alpha-crystallin were not associated with latency (P = 0.373). In contrast to the RD1-specific responses, the responses to PPD were not associated with clinical status (P > 0.17) but were strongly associated with positive tuberculin skin test results (>or=15-mm induration; P <or= 0.01). Our results suggest that RD1-specific IFN-gamma-secreting T-cell frequencies correlate with the presence of disease rather than with protective immunity in M. tuberculosis-infected individuals and do not distinguish recently acquired asymptomatic infection from remotely acquired latent infection.